Response of Super Early Pigeonpea to Varied Sowing Windows and Integrated Nutrient Management in Southern Telangana Zone - Kumar, M. Parimala; Devi, K. B. Suneetha; Naik, B. Balaji; Jayasree, G.; Sreekanth, P. D. (International Journal of Bio-resource and Stress Management, 2022)
The field experiments were conducted during kharif seasons (July–November) 2018 to determine the physiological, yield parameters and yield of super early pigeonpea under different sowing windows and with integrated nutrient management practices at Regional Agricultural Research Station, Palem, Telangana, India situated at 16˚ 51’ N Latitude and 78º25’ E Longitude with an average Altitude of 478 m above the mean sea level of Southern Telangana Zone of Telangana State, India. The experiment was laid out in strip plot design for pigeonpea with 3 main treatments i.e., (M1)1st July, (M2)20th July and (M3) 10th August sowings and four integrated nutrient management practices as sub treatments viz.S1: 75% RDF, S2:75% RDF+FYM enriched with microbial consortia (1 t ha-1), S3:100% RDFand S4:100% RDF+FYM enriched with microbial consortia (1 t ha-1) and replicated thrice. The findings of two years of field study revealed that, among the three sowing dates in main treatments, 1st July (M1) recorded a greater number of days to 50% flowering and 75% pod maturity of SEPP. Similar trend in the CGR, RGR, yield parameters and yield except 1000 seed weight of SEPP was noticed superior with 10th August sowing (M3) compared to other two sowing dates viz. July 1st and July 20th. The sub treatment containing INM practices revealed higher values of physiological, yield parameters and yield with application 100% RDF+FYM enriched with microbial consortia @ 1 t ha-1 (S4) compared to other INM practices.